Perilaku Anggota Subak Dalam Penggunaan Pupuk Organik Pada Budidaya Tanaman Padi Sawah (Kasus di Subak Dukuh, Desa Kapal, Kecamatan Mengwi, Kabupaten Badung) - I MADE SUDIANA; I GEDE SETIAWAN ADI PUTRA; I WAYAN SUDARTA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2016)
The Behavior of Subak’s Members in the Use of Organic Fertilizer on Rice Paddy Cultivation (A Case Study of Subak Dukuh, Kapal Village, Mengwi Sub-District of Badung Regency) The negative impact of consuming food containing excess of chemical residues has become the health issues lately. Environmental and food safety issues led to a lifestyle trend of going back to nature. Some individuals, groups, and organizations initiated the movement of environmentally friendly farming system namely organic farming. Seeing this condition, the researchers were interested in conducting research concerning the behavior of Subak’s members in the use of organic fertilizers in the cultivation of rice paddy. This research was conducted in Subak Dukuh which is located in the village of Kapal, Mengwi, Badung Regency. The selection of this region as the research location was done purposively. The populations of this research were members of Subak Dukuh totaling of 162 people. Determination of the sample size in this study using the formula of solvin so that the number of respondents taken were 35 people. The result shows that the level of knowledge of farmers on organic fertilizers was categorized as good achieving a score of 71.20 percent. But the behavior of farmers towards organic fertilizer was classified in the medium category with an average score of 66.20 percent. On the application of organic fertilizers, the farmers was in medium category with score of 63.80 percent. Based on the research results, it is suggested to the members of Subak as program implementers to apply or utilize the technology in the agricultural sector introduced by the extension workers, because before trying a new technology that given by the extension workers, farmers did not know whether the technology is good or not to be applied to their rice fields.